PERANCANGAN BUKU ILUSTRASI PENGENALAN GIZI PADA REMAJA - Ratna Indah Lestari S1 (Saraswati)
Nutrition is a chemical substance found in food that the body needs to produce energy, build and maintain the tissue, and manage the process of life. Consuming nutrients is of course very important for the body. Adolescence are the age where a dramatic change happens. Children grow with the relative same speed. It suddenly increases when they become teens. The growth is accompanied by hormonal, cognitive and emotional changes. All the changes require special nutrients. However, there are many obstacles hinder them from consuming nutritious food every day, the rise of fast food outlets and fast food commercials. Adolescence is the time at which someone always wants to try new things and tend to be unstable. Because of that a strategy is needed to divert the attention of teens who consume fast food turning to healty food.This book is designed to educated the tenagers about the importance of consuming healty food every day. All verbal and visual element in this book are made based on the teens style. In the future, it is expected that this book will help to reduce the rate of teens who suffer obesity and raice their awareness of how important consuming healty food is.Keywords: Nutrition, introduction, teens